Fluorescent and magnetic anti-counterfeiting realized by biocompatible multifunctional silicon nanoshuttle-based security ink. Issue 4 (12th January 2018) - Song, Bin; Wang, Houyu; Zhong, Yiling; Chu, Binbin; Su, Yuanyuan; He, Yao
Abstract : Herein, we present the first example of a silicon nanoshuttle-based security ink simultaneously featuring attractive optical and magnetic properties, suitable for fluorescent and magnetic anti-counterfeiting and encryption. Abstract : Herein, we present the first example of a silicon nanoshuttle-based security ink simultaneously featuring attractive optical and magnetic properties, suitable for fluorescent and magnetic anti-counterfeiting and encryption. Significantly, the information can be dual-encrypted through multi-color fluorescence and longitudinal ( T 1 )/transverse ( T 2 ) relaxation contrast by using the silicon nanoshuttle-based security ink. We further demonstrate the feasibility of this high-performance ink for practical application in banknote anti-counterfeiting.